VIDEO PROFILE SEBAGAI MEDIA PROMOSI PADA MTS AL-HUSNA YPIHN CURUG KABUPATEN TANGERANG - Sugeng Widada; Adi Kusuma Widya Tama; Nanda Lestari (UNIVERSITAS RAHARJA, 2020)
The technology and sophistication of social media is growing very fast, marketing is increasingly growing in proportion to the information needs of the community. Therefore we need an appropriate strategy to deliver information well, and be able to achieve success. The purpose of this study was to help MTS Al-Husna YPIHN in an effort to focus on new prospective students. The problem that occurs in marketing MTS Al-Husna YPIHN is the lack of effective media in delivering messages. The marketing used is only using a brochure, brochures and there is no media video profile that explains in full about the school profile, excellence, vision, mission, school achievements and school facilities. The method used is the method of data collection (Observation, Interview, Library Study) and the method of the Concept of Media Production (KPM). The results of this study were in the form of Vidio Profile of the MTS Al-Husna YPIHN school, which included all school profiles designed using Adobe Premier Pro and Adobe Photoshop software. Through the design of promotional media using this video profile will increase the interest of new prospective students to join MTS Al-Husna YPIHN every year and can be useful as a medium of information for the community.